Management and Fractal Analysis of Desiccation Cracks of Soils with Acid Contamination. (7th December 2020) - Wang, Xin; Yang, Binbin; Jin, Lichuang; Zhang, Zepeng; Xu, Xinyang
Abstract : Soil pollution due to acid contamination changes the chemical state of the soil and affects the water evaporation and desiccation cracking characteristics of the soil. The contamination of soils is becoming a serious problem due to increases in manufacturing, construction, and industrial activities, especially in and around urban areas. Soil pollution has become a global issue with serious and harmful impacts on the environment. The purpose of this paper is to present a study on the evaporation characteristics of soil contaminated with different acid concentrations. The result indicates that water evaporation in soils can be divided into three stages: the steady rate of evaporation, deceleration of evaporation, and residual evaporation stages. With increases in acid concentration, there is critical water content at which the rate of evaporation starts to decrease with increase in the duration of evaporation. Surface crack development in soils with different acid concentrations can be divided into three stages: initial cracking, crack development, and crack stabilization. When the acid concentration is higher than 0.4 mol/L, the initial cracking and stabilization stages disappear, and cracks continue to develop until they become stable.